2021
DOI: 10.1038/s41598-021-82363-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum carbohydrate antigen 19-9 levels and computed tomography severity score in patients with nontuberculous mycobacterial pulmonary disease

Abstract: There is no validated clinical biomarker for disease severity or treatment response for nontuberculous mycobacterial pulmonary disease (NTM-PD). We investigated the correlation between elevated serum carbohydrate antigen (CA) 19-9 levels and NTM-PD disease activity, defined using an imaging severity score based on chest computed tomography (CT). We retrospectively examined 79 patients with NTM-PD who underwent serum CA19-9 level assessments and chest CT less than 1 month apart. NTM-PD severity was rated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
1
1
Order By: Relevance
“…When we initially planned this study, our expectation was that higher serum CA19-9 levels would be linked to poorer treatment responses in NTM-PD patients, based on previous research indicating a positive correlation between serum CA19-9 levels and the extent of lung lesions observed in chest CT scans [22]. However, contrary to our initial expectations, our analysis revealed that elevated serum CA19-9 levels did not result in worse microbiological responses to antibiotic treatment.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…When we initially planned this study, our expectation was that higher serum CA19-9 levels would be linked to poorer treatment responses in NTM-PD patients, based on previous research indicating a positive correlation between serum CA19-9 levels and the extent of lung lesions observed in chest CT scans [22]. However, contrary to our initial expectations, our analysis revealed that elevated serum CA19-9 levels did not result in worse microbiological responses to antibiotic treatment.…”
Section: Discussioncontrasting
confidence: 73%
“…Interestingly, recent research findings have illuminated the potential elevation of CA19-9 in the context of chronic respiratory diseases, including bronchiectasis or pulmonary mycobacterial infections [20]. Furthermore, investigations have highlighted a notable decline in serum CA19-9 levels following antibiotic treatment in patients with NTM-PD, a phenomenon intricately linked to the severity of pulmonary computed tomography (CT) lesions [21][22][23]. Consequently, there is a growing interest in discerning the effective utilization of CA19-9 in the management of NTM-PD patients, which warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…When we initially planned this study, we anticipated that higher serum CA19-9 levels would be associated with poorer treatment responses in NTM-PD patients based on a study that found a positive association between serum CA19-9 levels and the extent of lung lesions on chest CT [8]. Contrary to our expectations, our analysis revealed that elevated serum CA19-9 levels did not lead to worse microbiological responses to antibiotic treatment.…”
Section: Discussioncontrasting
confidence: 63%
“…Interestingly, recent studies have reported that CA19-9 can also increase in chronic respiratory diseases, such as bronchiectasis or pulmonary mycobacterial infection [6]. Moreover, studies observed a decrease in serum CA19-9 levels after antibiotic treatment in NTM-PD patients, which has also been associated with the severity of pulmonary computed tomography (CT) lesions [7][8][9]. Thus, there is increasing interest in how CA19-9 can be used effectively in the management of NTM-PD patients.…”
Section: Introductionmentioning
confidence: 99%